Effects of Jatropha oil on rats following 28‐day oral treatment. Issue 7 (22nd December 2011) - Poon, Raymond; Valli, Victor E.; Nimal Ratnayake, W. M.; Rigden, Marc; Pelletier, Guillaume
ABSTRACT Jatropha oil is an emerging feedstock for the production of biodiesels. The increasing use of this nonedible, toxic oil will result in higher potential for accidental exposures. A repeated‐dose 28‐day oral toxicity study was conducted to provide data for risk assessment. Jatropha oil diluted in corn oil was administered by gavage to male and female rats at 0.5, 5, 50 and 500 mg kg−1 body weight per day for 28 consecutive days. Control rats were administered corn oil only. The growth rates and consumption of food and water were monitored. At necropsy, organs were weighed and hematological parameters assessed. Serum clinical chemistry and C‐reactive protein were measured and histological examinations of organs and tissues were performed. Markedly depressed growth rate was observed in males and females receiving Jatropha oil at 500 mg kg−1 per day. Decreased white blood cell and lymphocyte counts were detected in females at 50 and 500 mg kg−1 per day and in males at 500 mg kg−1 per day. These changes were correlated to mild and reversible histological changes in male and female spleens. In the liver, a mild increase in portal hepatocytes cytoplasm density was observed in males and females, while periportal vacuolation was observed exclusively in females. Mild acinar proliferation was observed in the female mammary glands at all dose levels. It is concluded that Jatropha oil produces adverse effects on female rats starting at 50 mg kg−1 per day with decreased white blood cell and lymphocyte counts and at 500 mg kg−1 per day in both genders in term of depressed growth rates. Copyright © 2011 John Wiley & Sons, Ltd.